Measurement of Thoracic Aortic Diameter Using Contrast-Enhanced CT Chest Based on Age, Gender, and Hypertension - Irma, Ade; Daulay, Elvita Rahmi; Lubis, Anggia Chairuddin (CoinReads Media Prima, 2023)
Introduction: CT is widely used to evaluate patients with aneurysm or aortic dissection. Therefore, it is very important to assess accurate aortic size in detecting aneurysm and dissection. The thoracic aortic diameter varies depending on the measurement level. Several demographic factors affect the thoracic aorta diameter such as age and gender. Risk factors for cardiovascular disease such as hypertension also have a relationship with the diameter of the thoracic aorta. To determine the difference of thoracic aorta diameter based on age, sex, and history of hypertension in patients with contrast-enhanced CT chest. Method: A case-control study in 140 patients with contrast-enhanced CT chest without signs or symptoms of car¬diovascular diseases. Thoracic aortic diameters were measured at seven predetermined levels on CT images. Analysis of data was performed with regard to age, sex, and hypertension. Results: The mean diameters of the thoracic aorta at the level of the aortic valve sinus is 3.06 ± 0.39 cm, ascending aorta 2.90 ± 0.39 cm, proximal to innominate artery 2.73 ± 0.39 cm, transverse aortic arch 2.53 ± 0.38, distal transverse aortic arch 2.37 ± 0.35, aortic isthmus 2.17 ± 0.33, and descending aorta at the level of diaphragm 1.91 ± 0.33 cm. There is a significant difference in all thoracic aortic diameters based on age and gender on statistical analysis (p<0.001). There is a significant difference in all thoracic aortic diameters between subjects with history of hypertension and without history of hypertension, except at the level of transverse aortic arch (p<0.051). Conclusion: There is a difference in the mean thoracic aortic diameter at each level of measurement based on age, sex, and history of hypertension in patients with contrast-enhanced CT chest.